Penetapan Kadar Air Dan Kadar Protein Pada Biskuit Yang Beredar Di Pasar Banjarbaru - Normilawati; Fadlilaturrahmah; Samsul Hadi; Normaidah (STIKES MUHAMMADIYAH KLATEN, 2019)
Many biscuits circulating in the community are not labeled and do not include the value of water and protein content in accordance with SNI. Therefore, it is necessary to determine the water content and protein content in the biscuits. Determination of water content and protein content in biscuits was carried out on 2 biscuit samples taken at the Banjarbaru Market. The water content test on the sample was carried out by the gravimetric method and the protein content test was carried out by the Kjeldahl method. The results obtained were the test of water content of 2 biscuit samples respectively at 4.43% and 3.84%. While the results of the protein content test from 2 samples are 5.31% and 6.89%, respectively. According to SNI 01-2973-2011 the water content limit does not exceed 5% while the protein content limit is a minimum of 5%. The results of 2 samples showed the water content and protein content in accordance with SNI.